PENGARUH TERPAAN IKLAN PARTAI PERINDO DAN BERITA SEPUTAR PARTAI PERINDO DI TELEVISI TERHADAP PERSEPSI PEMILIH PEMULA MENGENAI PARTAI PERINDO - Noor, Reza Muhammad (Interaksi: Jurnal Ilmu Komunikasi, 2017)
ABSTRACTIndonesia is a democratic and multiparty system or system that allows more than two political parties. It is guaranteed in Law No. 2 of 2008 on political parties where it is stated that freedom of association, assembly and expression of thoughts and opinions is a human right recognized and guaranteed by the 1945 Constitution of the Republic of Indonesia. With multiparty system and guarantees of the law, many emerging new political parties in Indonesia. One of them is Partai Persatuan Indonesia or abbreviated as Perindo. The party declared in 2015 is a party formed by Hary Tanoesoedibjo. As a new political party, Perindo Party must have support from the community. Some of the things that are done is to show the party ads and news about the party on television. According to data from the KPU, the largest number of voter-age voters is that the information in advertisements and news about Perindo Party on television is designed in such a way as to appeal to beginner voters. This study aims to determine how much influence the exposure of Perindo Party advertising and exposure of news about the Perindo Party on television to the perception of beginner voters regarding the Perindo Party. Theories used are the Advertising Exposure Theory, Informastion Exposure Theory, and the Uses and Gratification Theory. The population used is Diponegoro University FISIP students who have never participated in the election. While the sample taken is 60 people with purposive sampling method. Based on the analysis of regression analysis on Perx for Perindo Party Ads on Television (X1), Exposure of News Perindo Party on Television (X2), and Perception of Beginner Voters Regarding Perindo Party (Y), the result of regression coefficient value is 71,3% significance of Sig value. = 0.000 which means> significant criterion (0,05), Thus model of regression equation influence of variable X to variable Y is very high and significance between variables based on research data is very significant. Then it shows that there is a strong influence between Perpaan Iklan Perindo Party on Television (X1) and Terpaan Berita Seputar Perindo Party in Television (X2) to Perception of Beginner Voters Regarding Perindo Party (Y). The higher the exposure of Perindo Party advertisement on television and the exposure of Perindo Party news on television, the higher the perception of the beginner voters regarding Perindo Party. It is suggested that the advertising and information designs in the Perindo Party report be improved so that the results are better than now.Keywords: Ad Inclusion, Information, Perception, Beginner Voters, Perindo Party